2019
DOI: 10.12956/tchd.511789
|View full text |Cite
|
Sign up to set email alerts
|

Bi̇r Yeni̇doğanda Epi̇gnatus – Orofari̇ngeal Teratom

Abstract: Epignathus also known as oropharyngeal teratoma is a very rare tumor in newborns, which has a female predominance. The treatment is simple excision of the mass surgically which should not be delayed. We operated a male newborn due to intraoral mass causing episodic deglution and respiration problems. The histopathology was reported as epignathus and this case is discussed based on the current literature because of its rarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Although congenital oropharyngeal teratomas are considered rare benign tumors, when present, they can cause several sequelae in the child's oral cavity, as observed in this case report, requiring long-term multidisciplinary follow-up to correct them. This clinical case has many similarities with others found in the literature 2,[6][7][8]10,11,[15][16][17][18][19] . Regarding gender, most studies reported the presence of oropharyngeal teratomas in female children.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Although congenital oropharyngeal teratomas are considered rare benign tumors, when present, they can cause several sequelae in the child's oral cavity, as observed in this case report, requiring long-term multidisciplinary follow-up to correct them. This clinical case has many similarities with others found in the literature 2,[6][7][8]10,11,[15][16][17][18][19] . Regarding gender, most studies reported the presence of oropharyngeal teratomas in female children.…”
Section: Discussionsupporting
confidence: 81%
“…In this case, the removal of the teratoma was performed early, o the 17th day of life, requiring removal of the residual teratoma two weeks later. The tumor described in this case was classified anatomically and pathologically as mature, as well as the tumors reported by most authors 2,4,6,9,11,12,14,16,19,21,22 . However, even though it is an uncommon occurrence, Kumar et al 7 and Chung et al 8 reported cases of immature teratoma.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations